Frailty prevalence and its associations in a subacute geriatric ward in Singapore - Christine Yuanxin Chen; Thulasi Chandran; Vivian Cantiller Barrera; Rachelle Tumbokon Tan-Pantanao; Tanya Joy Zapata Quicho; Zin Tun Thant; Kiat Sern Goh (Singapore Medical Journal)
Introduction: Our aim was to study the prevalence of frailty and its associated factors in a subacute geriatric ward. Methods: This was a cross-sectional study of 167 participants between June 2018 and June 2019. Baseline demographics and participants’ Mini Nutritional Assessment, Geriatric Depression Scale, Mini Mental State Examination, Charlson’s Comorbidity Index and LACE index scores were obtained. Functional measurements such as modified Barthel’s Index scores and hand grip strength (HGS) were taken. Frailty was assessed using the Clinical Frailty Scale (CFS) and the FRAIL scale. Data on history of healthcare utilisation, medications, length of stay, selected blood investigations and presence of geriatric syndromes were also collected. Results: The prevalence of pre-frailty (CFS 4) and frailty (CFS ≥ 5) was 16.2% and 63.4%, respectively. There were significant associations between CFS and age (pre-frail vs. non-frail: odds ratio [OR] 1.14, 95% confidence interval [CI] 1.04–1.25, P = 0.006; frail vs. non-frail: OR 1.08, 95% CI 1.01–1.15, P = 0.021), HGS at discharge (frail vs. non-frail: OR 0.90, 95% CI 0.82–0.99, P = 0.025), serum albumin (frail vs. non-frail: OR 0.90, 95% CI 0.82–0.99, P = 0.035) and the presence of urinary incontinence (frail vs. non-frail: OR 3.03, 95% CI 1.19–7.77, P = 0.021). Conclusion: Frailty is highly prevalent in the subacute geriatric setting and has many associated factors. In this study, independent factors associated with frailty were age, HGS at discharge, serum albumin and urinary incontinence. This has implications for future resource allocation for frail older inpatients and may help direct further research to study the effectiveness of frailty-targeted interventions.